2007
DOI: 10.1021/jm070453f
|View full text |Cite
|
Sign up to set email alerts
|

N-Acylthiadiazolines, a New Class of Liver X Receptor Agonists with Selectivity for LXRβ

Abstract: We have identified a novel liver X receptor (LXR) agonist (2) that activates the LXRbeta subtype with selectivity over LXRalpha. LXRbeta selectivity was confirmed using macrophages derived from LXR mutant mice. Despite its selectivity and modest potency, the compound can induce APO-AI-dependent cholesterol efflux from macrophages with full efficacy. Our results indicate that it is possible to achieve significant LXRbeta selectivity in a small molecule while maintaining functional LXR activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…De novo lipid biosynthesis was assessed by 14 C-acetate (GE Healthcare/Amersham; 57 mCi/mmol, 0.2 Ci/ l) incorporation assays in cells grown in 6-well plates. Briefl y, cells were serum starved for 2 h in 1 ml DMEM/glucose followed by the addition of 1 Ci of 14 C-acetate and incubated for 4 h at 37°C, 5% CO 2 .…”
Section: Lipids Biosynthesis Analysis and Mass Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…De novo lipid biosynthesis was assessed by 14 C-acetate (GE Healthcare/Amersham; 57 mCi/mmol, 0.2 Ci/ l) incorporation assays in cells grown in 6-well plates. Briefl y, cells were serum starved for 2 h in 1 ml DMEM/glucose followed by the addition of 1 Ci of 14 C-acetate and incubated for 4 h at 37°C, 5% CO 2 .…”
Section: Lipids Biosynthesis Analysis and Mass Spectroscopymentioning
confidence: 99%
“…Briefl y, cells were serum starved for 2 h in 1 ml DMEM/glucose followed by the addition of 1 Ci of 14 C-acetate and incubated for 4 h at 37°C, 5% CO 2 . In some experiments, cells were pretreated for 30 min with either 50 M LY 294002 (PI3-kinase inhibitor), 50 M PD9805 [a mitogen-activated protein (MAP) kinase inhibitor], 0.1 M rapamycin (mTOR inhibitor), 10 M cerulenin (a fatty acid biosynthesis inhibitor), 20 g/ml lovastatin (a cholesterol biosynthesis inhibitor), 5 M H89 (protein kinase A inhibitor), 20 M compound C (AMP kinase inhibitor), or 10 M cytochalasin B (glucose transport inhibitor).…”
Section: Lipids Biosynthesis Analysis and Mass Spectroscopymentioning
confidence: 99%
“…[19] Furthermore, the crystal structures of the ligand binding domains of these receptors have revealed that the same amino acids line the pocket in both receptors. [22] LXRα is most highly expressed in the liver, kidney, intestine and adipose tissue, while the expression of LXRβ is detectable in every tissue tested at a fairly consistent level. When compared using real-time quantitative PCR, the expression of mouse LXRβ in the liver is approximately 2-fold less than that of LXRα, while in other tissues LXRβ is the predominant receptor.…”
Section: The Nuclear Hormone Receptors Lxrα and Lxrβmentioning
confidence: 88%
“…Progress has been made to generate LXRβ-selective ligands, a remarkable advance considering the amino acid residues lining the ligand binding pockets of LXRα and LXRβ are identical. [22] However, because of this considerable difficulty, it is unclear to what extent selectivity between the isoforms can be achieved and whether selectivity obtained from in vitro screening will be maintained in an in vivo setting. A further challenge will be to design LXRβ-selective ligands with pharmacokinetic properties amenable to development.…”
Section: Benefits and Challenges Of Targeting Lxr For Therapeutic Modmentioning
confidence: 99%
“…Structure-activity relationship (SAR) studies have been therefore conducted, resulting in the synthesis of different LXR agonists. Among them are acetyl-podocarpic acid and derivatives [79;80], 2-aryl-N-acyl indole [81], or N-acylthiadiazolines [82], anilinohexafluoroisopropanols [83], phenyl acetic acid substituted quinolines [12], acanthoic acid-related diterpenes [84], acidic heterocycles [85]. However, although most of these compounds are active on cholesterol metabolism, they also undesirably upregulate SREBP1-c gene expression, limiting therefore their development.…”
Section: Page 15 Of 35mentioning
confidence: 99%